Cypriot Literatures as Part of the Eastern Mediterranean Contact Area (1850-1960) - Kappler, Matthias (Études helléniques / Hellenic Studies, 2007)
The present contribution constitutes an attempt to consider “Cypriot literatures”, i.e. especially Greek Cypriot and Turkish Cypriot literature, as part of a contact area which covers the former Ottoman provinces in the Eastern Mediterranean (Greece, Anatolia, Lebanon, Syria, Palestine, Egypt) in order to analyze topics, settings and narrative discourse in a comparative approach. With the aid of concepts like “dislocation/migration” and “centre-periphery” patterns borrowed from post-colonial studies, this approach aims at providing convergent structures in literary expression in Cypriot literatures in comparison to Near Eastern (especially Arabic) literatures, and it tries to create links between peripheral literary expression in migration (for instance Greek Cypriots in Egypt) and central trends and currents during the last year of Ottoman rule and during the British rule on the island.